The Effect Of Work Discipline, Compensation, Occupational Health And Safety On Employee Job Satisfaction - Syardiansah Syardiansah; Dhian Rosalina; Febbie Nauly Yusmalita (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
A growing company should prioritizes discipline, compensation and employee safety and health to be able to produce employee satisfaction which can ultimately improve performance or positive results for the company. This study aims to determine the effect of work discipline, compensation and health and occupational health and safety on employee job satisfaction at PT Sisirau Aceh Tamiang Regency. The sample in this study were 52 respondents, which were all employees who were in the section under study. The data analysis method used is multiple linear regression analysis to see the effect of the relationship between each based variable and the dependent variable. The results showed that work discipline had a positive and significant effect on employee job satisfaction, compensation had a positive and significant effect on employee job satisfaction, and occupational health and safety had a positive and significant effect on employee job satisfaction.Keywords: work discipline, compensation, occupational health and safety, job satisfaction